Superalloys : a technical guide - Donachie, Matthew J. (ASM International, 2002)
Superalloys provide the most reliable and cost-effective means of achieving high operating temperature and stress conditions in aircraft and industrial gas turbines and in a wide variety of other applications. This book covers virtually all technical aspects related to the selection, processing, use, and analysis of superalloys. The text of this new second edition has been completely revised and expanded with many new figures and tables added. In developing this new edition, the focus has been on providing comprehensive and practical coverage of superalloys technology. Some highlights include the most complete and up-to-date presentation available on alloy melting. Coverage of alloy selection provides many tips and guidelines that the reader can use in identifying an appropriate alloy for a specific application. The relation of properties and microstructure is covered in more detail than in previous books.
Keywords: Heat resistant alloys.; elektronické knihy; electronic books